Business applications software for ibm and compatible microcomputers - Ingalsbe, Lon. ([S.l.] : Macmillan Pub Co, 1991)
The "Ingalsbe Business Applications Software Textbook Series" consists of texts/tutorials offering hands-on coverage of the most popular applications software packages for IBM and compatible microcomputers. In each volume, a modular organization presents applications software concepts in a standardized format that includes: introduction and key terms; tutorial exercises; operation and command summary; advanced topics; a "hints and hazards" section as well as study problems and questions. These are followed by background discussion materials and numerous practice exercises. The proven, step-by-step tutorials get students at the computer, and learning functions and commands, almost immediately - with minimal instructor involvement.